PENGARUH UMUR BIBIT DAN PUPUK N, P, K TERHADAP PADI VARIETAS IR 42 DI LAHAN PASANG SURUT DENGAN METODE SRI DI DESA KUALA MULYA KECAMATAN KUALA CENAKU - Rahmat ' Hidayah; Jurnawaty ' Sofjan; Wardati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Research aims to understand bedween the ages of fertilizer and seeds N, P, K and interaksi to growth and the production of rice varieties ir in land tides on village Kuala Mulya Cinaku with the methods SRI. The study analyzed uses the design faktorials design random group consisting two factors thas is, factors first age seeds consisting three the economic situation, the second faktor four the economic situation and three remedial. The results of the analisis factor age fertilizer and seeds N, P, K had have real inpact on saplings maximum, heaviy dry, age out panicles, the number of grain panicles, heavy grain dry ground and heavy 1000 grains. Interaction age fertilizer and seeds N, P, K inpact to age out panicles, the amount of grain panicles, heavy gaba dry steamroller, and heavy 1000 grains of the rice plant varieties IR 42. Seeds age 7 day and fertilizer 50 kg Urea, 25 kg SP-36, 25 kg give grownth KCl better with the production of dried grain 2.388,50 kilogram/plot. Against interaction bedween treatment age seed and fertilizer N, P, K treatment and production Seeds age 7 day and fertilizer 50 kg Urea, 25 kg SP-36, 25 kg give grownth KCl most excellent. Key word: rice varities IR 42, age fertilizer and seeds N, P, K